2017
DOI: 10.1177/1049909117701695
|View full text |Cite
|
Sign up to set email alerts
|

Compassion Fatigue Among Palliative Care Clinicians: Findings on Personality Factors and Years of Service

Abstract: Personality traits of neuroticism and agreeableness may convey risk and resilience, respectively, for palliative care professionals. More research is needed to determine if assessing personality traits can help identify providers at risk for adverse reactions to patient trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 27 publications
0
49
0
5
Order By: Relevance
“…It is understandable therefore that nurses may detach from their patients and adopt a more ‘technical’ approach to care, in order to protect themselves from emotional attachments that will be disrupted when the patient becomes less well and consequently dies. However, while this may be effective as a coping strategy, nurses who empathise less with patients are less likely to develop a sense of meaning or purpose in their work,49 which, according to our findings, is key to maintaining and enhancing resilience.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…It is understandable therefore that nurses may detach from their patients and adopt a more ‘technical’ approach to care, in order to protect themselves from emotional attachments that will be disrupted when the patient becomes less well and consequently dies. However, while this may be effective as a coping strategy, nurses who empathise less with patients are less likely to develop a sense of meaning or purpose in their work,49 which, according to our findings, is key to maintaining and enhancing resilience.…”
Section: Discussionmentioning
confidence: 60%
“…O’Mahony et al 49 describe how the effects of repeated exposure to loss and suffering in palliative care clinicians may be cumulative, leading to clinically significant levels of distress. Furthermore, they found that nurses who are overly empathic have higher prevalence of secondary traumatic stress and compassion fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…In industrial workers it has been shown that the effects of insomnia on accident risk can be increased by occupational fatigue [ 38 ]. Sustained occupational effort, prolonged hours of work and night shifts, irregular life habit, and exposure to traumatic events, that are very common in commercial drivers, have been associated with sleep disorders in other high-risk occupations such as prison personnel [ 39 ] and health care workers [ 40 42 ]. In all these occupational examples, researchers observed significant individual vulnerability to performance impairment caused by loss of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the clinicians in our study described themselves as resilient and were able to overcome burnout with their own coping strategies. Similarly, O'Mahony et al 22 shared that those who had more years of service in palliative care were less burnt out and experienced better job satisfaction. This may be due to survival bias where those who experienced burnout or felt that this work was not suitable for them opted to leave the field.…”
Section: Main Findingsmentioning
confidence: 99%